Komunikasi Persuasif Ceo Coffee Shop Dalam Menarik Minat Investor - Muhammad Fariz Firdaus; Yanti Tayo; Muhammad Ramdhani (Peneliti.net, 2023)
Mahakan Coffee is a coffee shop in the Cisarua Puncak Bogor area. The purpose of this research is to find out how to communicate persuasively from the CEO of Mahakan Coffee to attract other people to invest in Mahakan Coffee and find out what obstacles are experienced when the persuasive communication process occurs. This journal uses a qualitative approach to determine how to find, collect, process and analyze research data. From the results of field research, it can be concluded that in the process of persuasive communication, the CEO of Mahakan Coffee approaches in several ways, namely psychodynamics by persuading people who have previously had high trust with the CEO of Mahakan Coffee, sociocultural by utilizing friendships to broaden the delivery of information and gain trust more, and finally the meaning construction CEO Mahakan Coffee provides a simple understanding without changing the meaning by making marketing sentences that aim to make it easier for the communicant to understand the meaning of this and also of course to attract more attention from the communicant.